2014
DOI: 10.1038/srep07041
|View full text |Cite|
|
Sign up to set email alerts
|

A reduction in reactive oxygen species contributes to dihydromyricetin-induced apoptosis in human hepatocellular carcinoma cells

Abstract: Reactive oxygen species (ROS) and cellular oxidant stress are considered inducers of carcinogenesis. However, the association of ROS with cancer is both complex and, at times, paradoxical. We assessed the effects of dihydromyricetin (DHM) on the induction of ROS accumulation and on the activation of the mitochondrial signaling pathway in human hepatoma HepG2 cells. The results indicated that DHM could reduce ROS accumulation in a concentration-dependent manner. Additionally, with increasing concentrations of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…DHM has been shown to be a potent anti-oxidative agent and to protect mitochondrial functions [13,14] . In addition, recent studies have reported that DHM has anti-tumor and anti-inflammatory effects [15][16][17][18] . Interestingly, DHM can also protect PC12 cells from oxidative stress and elicit beneficial effects in both Alzheimer's disease and alcohol intoxication [13,19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…DHM has been shown to be a potent anti-oxidative agent and to protect mitochondrial functions [13,14] . In addition, recent studies have reported that DHM has anti-tumor and anti-inflammatory effects [15][16][17][18] . Interestingly, DHM can also protect PC12 cells from oxidative stress and elicit beneficial effects in both Alzheimer's disease and alcohol intoxication [13,19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of lipopolysaccharide-activated macrophages, low doses of Amp effectively suppressed ROS generation and the release of inflammatory cytokines (25). Low-dose Amp has also been demonstrated to inhibit phosphoinositide 3-kinase activation without attenuating MAPK (ERK, JNK and p38-MAPK) activation (25), and Amp-mediated ROS reduction has been identified to trigger the apoptosis of hepatocellular carcinoma cells (48). These results indicate that effective chemotherapeutic doses will need to be carefully determined and that mechanism(s) of action must be elucidated within each dose range and for each cell type to mitigate the risk of pleiotropic effects.…”
Section: Discussionmentioning
confidence: 94%
“…ROS cause ER stress, which results in the generation of more ROS (45,47). Although Amp-mediated ROS trigger ER stress/AMPK activation and JNK/p38-MAPK signaling, leading to apoptosis in colon cancer cells, it is important to consider that Amp is not necessarily pro-ROS in all circumstances (25,48). In a previous study of lipopolysaccharide-activated macrophages, low doses of Amp effectively suppressed ROS generation and the release of inflammatory cytokines (25).…”
Section: Discussionmentioning
confidence: 99%
“…DHM is the primary medicinal flavonoid extracted from Ampelopsis grossedentata . Recent studies showed that DHM has many biologic effects, including anti‐alcohol intoxication, reducing blood pressure, and antibacterial, anti‐inflammatory, and antitumor properties (Zhong et al, ; Zhang et al, ; Murakami et al, ; Luo et al, ; Qi et al, ; Liu et al, ; Zeng et al, ; Zhao et al, ; Ji et al, ; Jiang et al, ). Our studies demonstrated that DHM exhibits antitumor activity in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, DHM has attracted the attention of many researchers due to its wide range of pharmacological activities such as anti‐inflammatory, cough‐relieving, anti‐hypertensive, antioxidative, hypoglycemic, and hepatoprotective effects (Zhong et al, ; Zhang et al, ; Murakami et al, ; Qi et al, ). Recently, it was shown that DHM possesses antitumor effects, such as anti‐proliferation, cell‐cycle arrest, induction of apoptosis, anti‐migration/invasion, and anti‐angiogenesis in several cancer types including melanomas, gastric cancer, hepatoma, and osteosarcomas (Luo et al, ; Liu et al, ; Zeng et al, ; Zhao et al, ; Ji et al, ; Jiang et al, ). Moreover, DHM can reverse multidrug resistance and increase sensitivity to chemotherapeutic drugs in leukemia and osteosarcomas through regulating p‐glycoprotein and AMP‐activated protein kinase, respectively (Ye et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%